Clinical phenotypes study of 231 children with Williams syndrome in China: A single‐center retrospective study. Issue 12 (27th September 2022) - Li, Fang‐fang; Chen, Wei‐jun; Yao, Dan; Xu, Lin; Shen, Ji‐yang; Zeng, Yan; Shi, Zhuo; Ye, Xiao‐wei; Kang, Dao‐huan; Xu, Bin; Shao, Jie; Ji, Chai
Abstract: Background: Williams syndrome (WS) is a multisystem neurodevelopmental disorder caused by microdeletions in 7q11.23. This study aims to characterize the clinical phenotypes of Chinese children with WS to help for the early diagnosis and intervention of this disease. Methods: 231 children diagnosed with WS were retrospectively recruited to the study. Clinical data were analyzed to obtain the incidence of different clinical phenotypes. The occurrence of phenotypes and the influence of gender and age on the incidence of different phenotypes were analyzed. Results: All WS exhibited facial dysmorphism (100.0%). The majority had neurodevelopmental disorder (91.8%), hoarseness (87.4%) and cardiovascular anomalies (85.7%). The incidence of short stature (46.9%), inguinal hernia (47.2%), hypercalciuria (29.10%), hypercalcemia (9.1%), subclinical hypothyroidism (26.4%) and hypothyroidism (7.4%) were relatively higher. Gender differences were found in supravalvular aortic stenosis (SVAS, p < .001), ventricular septal defect (VSD, p < .05), inguinal hernia ( p < .001), superior pulmonary stenosis (SVPS, p < .05) and neurodevelopmental disorder ( p < .05). The incidence of neurodevelopmental disorder in WS increased with age ( p < .05) while cardiovascular anomalies ( p < .001), short stature ( p < .001), hypercalciuria ( p < .001) and hypercalcemia ( p < .01) decreased with age. Conclusions: Facial dysmorphism, neurodevelopmental disorder, hoarseness and cardiovascular anomalies were the most common phenotypes. Genetic testing should be suggested to confirm the diagnosis for children with the above abnormalities. Gender and age should be taken into account when making diagnosis and intervention. Abstract : This study collected clinical data of a large sample of children with William syndrome, and obtained phenotypic incidence, disease outcome and gender differences, which will be helpful for disease diagnosis and follow‐up, and also point out the direction for further research.